Approche socio-historique de la filière Miage et effets de l’alternance sur l’enseignement des SHS - Marie Carcassonne; Laurence Servel (Revue Internationale de Pédagogie de l’Enseignement Supérieur)
Apprenticeship has expanded steadily over the past few years in France, including university in highly selective programs. Starting with a comparative situation in which the same course entitled « Organization and Communication» has been given to students in initial training and in apprenticeship, we analyse why this course was received differently by students. The latter were enrolled in the first year of the Master Miage (Computer Methods Applied to Business Management) in a Parisian university. Firstly, we explore the framework in which this course is delivered. We show how the Miage apprenticeship training takes place in a particular context that greatly values the professionalization of students. Secondly, we present the socio-demographic specificities of this Miage apprenticeship population compared to the initial training one. A statistical analysis demonstrates that the apprentices are over-selected and represent a group endowed with a stronger academic background. Finally, taking into account these contextual elements and the specific features of this population, we highlight the fact that this group is facing temporal conflicts that lead teachers to modify their pedagogical practices and to adopt the role of tutors. This means to adapt the time required to present theoretical knowledge and it poses the significant issue of its assimilation.